'Essentials 4 Data Support': Five years' experience with data management training. (December 2016) - Verbakel, Ellen; Grootveld, Marjan
This article describes a research data management course for support staff such as librarians and IT staff. The authors, who coach the participants, introduce the three course formats and describe the training in more detail. In the last years over 170 persons have participated in this training. It combines a wealth of online information with face-to-face meetings. The aim of the course is to support the participants in strengthening various skills and acquiring knowledge so they feel confident to support, advise and train researchers. Interaction among the students is embedded in the structure of the training, because we regard it as a valuable instrument to develop a professional network. Recently the course has taken on a new challenge: in addition to the regular courses a couple of in house trainings have been delivered on request. The paper ends with a description of the key group assignments for such compact trainings.